2003
DOI: 10.1002/oa.694
|View full text |Cite
|
Sign up to set email alerts
|

Morphological description, biometry and phylogenetic position of the skull of Ngawi 1 (east Java, Indonesia)

Abstract: The skull of Ngawi 1 was discovered fortuitously in August 1987 on the left bank of the river Solo near the village of Selopuro (east Java, Indonesia). It is a complete, well preserved and strongly mineralized calvaria. The present article provides a complete description of this specimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…They concluded that Ngawi 1 is "a member of Ngandong and Sambungmacan group of H. erectus" mainly because of the shared high and rounded vault shapes and a few other surface characters. Widianto and Zeitoun (2003) and Zeitoun et al (2010) conducted cladistic analyses using "123 morphological and 345 metrical features" and reached the same conclusion as Widianto et al (2001), although unknown intercharacter correlations are a potentially significant source of error in this type of analysis. Zeitoun et al (2010) also conducted a 3-D geometric morphometric analysis based on 17 calvarial landmarks.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…They concluded that Ngawi 1 is "a member of Ngandong and Sambungmacan group of H. erectus" mainly because of the shared high and rounded vault shapes and a few other surface characters. Widianto and Zeitoun (2003) and Zeitoun et al (2010) conducted cladistic analyses using "123 morphological and 345 metrical features" and reached the same conclusion as Widianto et al (2001), although unknown intercharacter correlations are a potentially significant source of error in this type of analysis. Zeitoun et al (2010) also conducted a 3-D geometric morphometric analysis based on 17 calvarial landmarks.…”
Section: Introductionmentioning
confidence: 86%
“…The morphology of Ngawi 1 has been described in some detail by Sartono (1991), Widianto et al (2001), Widianto and Zeitoun (2003), Schwartz and Tattersall (2003), and Durband (2007), although detailed descriptions of the mandibular fossa (temporomandibular joint), foramen ovale, and some other cranial base features were not possible because of the remaining matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the morphology of the mandibular fossa supports the notion of discontinuity between the Ngandong/ Sambungmacan fossils and later modern humans in Australasia. The presence of this autapomorphy, among others described above and elsewhere (e.g., Durband, 2002bDurband, , 2004aDurband, ,b, 2005Durband, , 2007Baba et al, 2003Baba et al, , 2004, suggests that the population represented by the Ngandong and Sambungmacan fossils changed considerably from those forms sampled at Trinil and Sangiran and likely went extinct without contributing to the gene pool of modern humans; perhaps after undergoing a speciation event (e.g., Zeitoun, 2002;Durband, 2002bDurband, , 2004aDurband, ,b, 2005Durband, , 2007Widianto and Zeitoun, 2003). This scenario is in accord with paleoecological evidence compiled by Storm (2000Storm ( , 2001a suggesting that the Ngandong hominids went extinct as part of a faunal turnover on Java at approximately 126 kyr, a date that has been supported recently by Westaway and colleagues (2007).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the range of dates for Sambungmacan encompasses the Early to Late Pleistocene and may predate, post-date, or be synchronous with Ngandong. The Ngawi calvaria is also frequently grouped with Ngandong and Sambungmacan on the basis of shared morphology (Widianto and Zeitoun, 2003;Baab, 2016b) but there is no date available for this fossil.…”
Section: Geochronologymentioning
confidence: 99%
“…More recent work that has focused on the cranial morphology of the Asian H. erectus fossil record includes evaluations of the metric and non-metric diversity of Asian or specifically the Indonesian fossil record Kaifu et al, 2008), cranial shape variation in the Asian fossils (Baab, 2010;Zeitoun et al, 2010), and analyses focused on the affinities of particular fossils (Delson et al, 2001;Widianto et al, 2001;Widianto and Zeitoun, 2003;Durband, 2006;Kaifu et al, 2006Kaifu et al, , 2015Indriati and Antón, 2010). It was demonstrated that Asian, along with numerous African and Georgian fossils assigned to H. erectus, were distinct from or displayed minimal overlap with other archaic Homo species on the basis of threedimensional (3D) neurocranial shape (Zeitoun et al, 2010;Baab, 2016b).…”
Section: Introductionmentioning
confidence: 99%